Differences in explosive strength values for students of the faculty of physical education and sports (male) according to body mass index levels - George D. Mocanu; Gabriel Murariu; Vladimir Potop (Pedagogy of Physical Culture and Sports, 2023)
Background and Study Aim. Explosive strength/muscular strength is demanded at the level of different body segments and regions in most sports. The purpose of the research: is to identify the differences in the manifestation of explosive force between groups of underweight, normal weight and overweight university students; to determine the associations between the anthropometric parameters and the value of the results in the applied tests.